2022
DOI: 10.3390/molecules27144501
|View full text |Cite
|
Sign up to set email alerts
|

Development of Small-Molecule Fluorescent Probes Targeting Enzymes

Abstract: As biological catalysts, enzymes are vital in controlling numerous metabolic reactions. The regulation of enzymes in living cells and the amount present are indicators of the metabolic status of cell, whether in normal condition or disease. The small-molecule fluorescent probes are of interest because of their high sensitivity and selectivity, as well as their potential for automated detection. Fluorescent probes have been useful in targeting particular enzymes of interest such as proteases and caspases. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Previous studies have confirmed that proteins can effectively release peptides after enzymatic hydrolysis via biological proteases [ 40 ]. However, the peptides released by different enzymatic methods differ in content and quantity due to the specificity of proteases, followed by the yield of short peptides, which is an important indicator reflecting the effect of enzymatic hydrolysis and is closely related to the extent of hydrolysis [ 41 ]. It can be seen in Figure 5 that PeCTHC had a higher short peptide yield of 28.01 ± 1.45%.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have confirmed that proteins can effectively release peptides after enzymatic hydrolysis via biological proteases [ 40 ]. However, the peptides released by different enzymatic methods differ in content and quantity due to the specificity of proteases, followed by the yield of short peptides, which is an important indicator reflecting the effect of enzymatic hydrolysis and is closely related to the extent of hydrolysis [ 41 ]. It can be seen in Figure 5 that PeCTHC had a higher short peptide yield of 28.01 ± 1.45%.…”
Section: Resultsmentioning
confidence: 99%
“…Grad characteristic and can discriminate Ga 3+ and Pa 2+ in H 2 O/DMF (1/9, v/v) solution [33]. Compared with other analytical skills, the technology of fluorescent sensing has garnered significant attention due to its high sensitivity, fast response, excellent selectivity, and low biological toxicity [34][35][36][37][38][39][40][41]. However, practical applications still face inconveniences such as complex preparation, cumbersome separation, and challenging purification processes [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Through this initiative, we have made substantial contributions to the field, having developed over 30 bioprobes ( Figure 1 ) [ 6 ]. Conventionally, fluorescent probe development focuses on binding to proteins, a method we termed Protein-Oriented Live-cell Distinction (POLD) [ 7 , 8 , 9 , 10 ]. Throughout the procedure, the protein-binding system encounters limitations in explaining the journey of fluorescent molecules, particularly in the absence of protein partners.…”
Section: Introductionmentioning
confidence: 99%